2021
DOI: 10.1038/s41380-021-01164-4
|View full text |Cite
|
Sign up to set email alerts
|

Lithium increases mitochondrial respiration in iPSC-derived neural precursor cells from lithium responders

Abstract: Lithium (Li), valproate (VPA) and lamotrigine (LTG) are commonly used to treat bipolar disorder (BD). While their clinical efficacy is well established, the mechanisms of action at the molecular level are still incompletely understood. Here we investigated the molecular effects of Li, LTG and VPA treatment in induced pluripotent stem cell (iPSC)-derived neural precursor cells (NPCs) generated from 3 healthy controls (CTRL), 3 affective disorder Li responsive patients (Li-R) and 3 Li non-treated patients (Li-N)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 76 publications
(88 reference statements)
2
40
0
Order By: Relevance
“…To our knowledge, there are no studies assessing the direct effect of lithium on the PPP; nevertheless, its effects on the mitochondrial electron transport chain have been reported previously. Indeed, lithium was shown to promote the activity of three respiratory chain enzymes, complexes I, II, and III in the human frontal cortex [ 58 , 59 ]. Thus, it is possible that lithium altered mitochondrial homeostasis, which caused changes in the NADPH/NADP + ratio [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, there are no studies assessing the direct effect of lithium on the PPP; nevertheless, its effects on the mitochondrial electron transport chain have been reported previously. Indeed, lithium was shown to promote the activity of three respiratory chain enzymes, complexes I, II, and III in the human frontal cortex [ 58 , 59 ]. Thus, it is possible that lithium altered mitochondrial homeostasis, which caused changes in the NADPH/NADP + ratio [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cells were derived from three patients responders to lithium, three patients not exposed to lithium and three controls. Intriguingly, while the authors found a nonsignificant tendency for lower OCR in cells derived from lithium responder patients compared with controls, in vitro treatment with lithium improved OCR levels by enhancing maximal respiration and reserve capacity exclusively in cells derived from lithium responders [105].…”
Section: Discussionmentioning
confidence: 87%
“…This is for instance the case of mitochondria [104]. Indeed, a recent study explored the effect of in vitro treatment with lithium on oxygen consumption rate (OCR) and glycolytic rate (two indexes of mitochondrial respiratory function) in iPSC derived neural precursor cells (NPCs) [105]. Cells were derived from three patients responders to lithium, three patients not exposed to lithium and three controls.…”
Section: Discussionmentioning
confidence: 99%
“…We discuss that the underlying mechanisms might be associated with the aetiology of major depressive disorder. Mitochondrial alterations or altered energy metabolism in iPSC-derived neural lineages has already been studied [24][25][26][27][28][29][30] , but to the best of our knowledge, this is the first report addressing altered energy metabolism in iPSC-derived neural lineages in the context of major depression.…”
Section: Introductionmentioning
confidence: 99%